(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The transition from traditional teacher-centred instruction to modern, learner-centred pedagogical approaches has become a defining feature of contemporary education. This article investigates the use of modern teaching methods and their positive effects on student performance, engagement, and skill development. A qualitative review of recent empirical research was conducted to examine instructional strategies including flipped classrooms, active learning, collaborative learning, and technology-enhanced teaching. The analysis demonstrates that these methods contribute to improved academic achievement, increased learner motivation, and deeper conceptual understanding when compared to conventional lecture-based models. Active learning and collaborative approaches were found to enhance critical thinking and communication skills, while technology integration supported personalised learning and immediate feedback. Although challenges such as insufficient teacher preparation and limited technological resources persist, the overall evidence supports the effectiveness of modern pedagogical practices across diverse educational contexts. The study underscores the importance of strategic instructional design and professional development in maximising the benefits of innovative teaching methods. The findings offer theoretical and practical insights for educators, curriculum designers, and policymakers aiming to improve learning outcomes in higher education and secondary schooling.